Migration and translocal learning. Poles in Reykjavik - Zielinska, Malgorzata Karolina (University Electronic Press, 2019)
The paper analyses learning from the perspective of migration. It is based on a qualitative study of Polish first-generation migrants in Iceland. The theoretical framework adopted is translocal learning and learning from places – which joins the perspective of social learning with learning from the environment. The empirical material was used to construct eight categories showing translocal learning outcomes: practical skills, communicative competences, analytic competence, assimilation of values, selfconfidence, independence, living with uncertainty and mobility skills. The findings show that translocal learning has a critical potential of challenging the dominant ideology. Some of the learning outcomes help migrants in further migration. Finally, the author suggests a new concept for future research – translocal pedagogy. (DIPF/Orig.)